2007
DOI: 10.1111/j.1524-6175.2007.07161.x
|View full text |Cite
|
Sign up to set email alerts
|

Centrally Acting Antihypertensive Agents: An Update

Abstract: Centrally acting agents stimulate α2 receptors and/or imadozoline receptors on adrenergic neurons situated within the rostral ventrolateral medulla and, in so doing, sympathetic outflow is reduced. Centrally acting agents also stimulate peripheral α2 receptors, which, for the most part, is of marginal clinical significance. Central a agonists have had a lengthy history of use, starting with α‐methyldopa, which has had a dramatic decline in use, in part, because of bothersome side effects. Patients who require … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
70
0
10

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(80 citation statements)
references
References 42 publications
0
70
0
10
Order By: Relevance
“…In some countries, β-adrenoceptor blockers are prescribed to block 26 sympathetically mediated release of renin from the kidney (Wong et al, 2016). Calcium channel 27 blockers and α1-adrenoceptor antagonists reduce vascular resistance (Cubeddu, 1988;Tocci et al, 28 2015), while centrally-acting sympatholytic drugs such as the α2-adrenoceptor agonist clonidine and 29 the imidazoline receptor agonist moxondine, lower sympathetic activity (Sica, 2007). The clinician 30 will typically follow a nationally-agreed protocol for drug type, dose and sequence/combinations 31 …”
Section: Do We Need New Treatments For Hypertension?mentioning
confidence: 99%
“…In some countries, β-adrenoceptor blockers are prescribed to block 26 sympathetically mediated release of renin from the kidney (Wong et al, 2016). Calcium channel 27 blockers and α1-adrenoceptor antagonists reduce vascular resistance (Cubeddu, 1988;Tocci et al, 28 2015), while centrally-acting sympatholytic drugs such as the α2-adrenoceptor agonist clonidine and 29 the imidazoline receptor agonist moxondine, lower sympathetic activity (Sica, 2007). The clinician 30 will typically follow a nationally-agreed protocol for drug type, dose and sequence/combinations 31 …”
Section: Do We Need New Treatments For Hypertension?mentioning
confidence: 99%
“…This induces central inhibition of norepinephrine (NE) via the attenuation of NE release from terminals and firing from cell bodies in the locus coeruleus (Engberg and Eriksson, 1991). Guanfacine also promotes a downregulation of sympathomimetic outflow from the vasomotor center of the brain to the heart (Sica, 2007). Notably, extensive preclinical and clinical research has shown that both of these central and peripheral mechanisms may have a salient role in the reduction of cocaine craving, owing to the fact that activation of the lateral tegmental NE system Erb, 2010;Sinha et al, 2011;Mantsch et al, 2013) and autonomic peripheral arousal (Sinha et al, 2003;Fox et al, 2008b) are implicated in stress-induced motivation for, and relapse to, cocaine during early recovery.…”
Section: Introductionmentioning
confidence: 99%
“…46 In humans, the plasma NE level may be elevated in some hypertensives, 47 and drugs that lower the plasma level of NE, such as clonidine and the other a2 adrenergic agonists, reduce blood pressure. 48 And a strain of spontaneously hypertensive rats shows elevations in both tissue NE levels and rates of chemically induced tumorigenesis. 49 A sixth line of evidence is that excessive body weight is associated with adrenoceptor polymorphisms and elevated blood NE, 50 and it is also a risk factor for some adult cancers.…”
Section: Literature Search Detailsmentioning
confidence: 99%